2020
DOI: 10.1177/1934578x20977364
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacology Study of the Anticervical Cancer Mechanisms of FDY003

Abstract: Increasing data support that herbal medicines are beneficial in the treatment of cervical cancer; however, their mechanisms of action remain to be elucidated. In the current study, we used a systems pharmacology approach to explore the pharmacological mechanisms of FDY003, an anticancer herbal formula comprising Lonicera japonica Thunberg, Artemisia capillaris Thunberg, and Cordyceps militaris (Linn.) Link, in the treatment of cervical cancer. Through the pharmacokinetic assessment of absorption-distribution-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 165 publications
1
24
0
Order By: Relevance
“…Although the application of herbal drugs for GC treatment has gained increasing attention [5][6][7][8] , their complex multicomponentmultitarget mechanistic properties have yet to be investigated. In this study, we dissected the anti-GC properties of the herbal drug FDY003 through a systems perspective [9][10][11] . We found that FDY003 suppressed the viability and enhanced the chemosensitivity of human GC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the application of herbal drugs for GC treatment has gained increasing attention [5][6][7][8] , their complex multicomponentmultitarget mechanistic properties have yet to be investigated. In this study, we dissected the anti-GC properties of the herbal drug FDY003 through a systems perspective [9][10][11] . We found that FDY003 suppressed the viability and enhanced the chemosensitivity of human GC cells.…”
Section: Discussionmentioning
confidence: 99%
“…FDY003 is an anticancer herbal drug composed of Cordyceps militaris (Cm), Artemisia capillaris Thunberg (AcT), and Lonicera japonica Thunberg (LjT) [9][10][11] . It suppresses growth and promotes apoptosis in various cancers by targeting crucial genes and proteins associated with cancerous behaviors [9][10][11] . However, the anticancer effects of FDY003 on GC and the mechanisms involved need to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…FDY003, which is made up of Lonicera japonica Thunberg (LjT), Cordyceps militaris (Cm), and Artemisia capillaris Thunberg (AcT), is an herbal drug that exerts anticancer activity [ 9 11 ]. This herbal drug has antiproliferative and apoptosis-promoting properties in a variety of cancer types by pharmacologically modulating cancer-associated genes and proteins that regulate and promote key protumorigenic cellular processes [ 9 11 ]. However, the anti-PC potential of FDY003 and the underlying mechanisms remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 FDY003-an herbal mixture made up of Artemisia capillaris Thunberg (AcT), Cordyceps militaris (Linnaeus) Link (Cm), and Lonicera japonica Thunberg (LjT)-has been developed for cancer treatment and effectively triggers growth arrest and apoptosis in cancer cells. [5][6][7][8] This herbal drug exhibits a multiple compound-multiple target-multiple pathway mechanism of action by regulating various crucial cancer-associated gene, proteins, and pathways to exert its anticancer effects and to act as a chemosensitizer. [5][6][7][8] However, the pharmacological roles and regulatory mechanisms of FDY003 in EC have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] This herbal drug exhibits a multiple compound-multiple target-multiple pathway mechanism of action by regulating various crucial cancer-associated gene, proteins, and pathways to exert its anticancer effects and to act as a chemosensitizer. [5][6][7][8] However, the pharmacological roles and regulatory mechanisms of FDY003 in EC have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%